The price of parenthood: Surrogacy and Sweden’s obligations under the ECHR - Stafström,Alva (2025)
While Swedish families cannot conduct a surrogacy arrangement in the do- mestic health care system, it is possible to employ a surrogate abroad with the help of an agency. Such practices are however unregulated, both internation- ally and in the Swedish legal system. Additionally, the human rights issues associated with surrogacy have long been debated and cases of exploitation of both surrogates and children have been reported in the news. More re- cently, the UN special rapporteur on violence against women and girls issued a report that called for a total abolition of surrogacy worldwide through crim- inalization of the practice. This thesis aims to assess if Sweden has an obligation to create a legal frame- work that regulates surrogacy stemming from the European Convention on Human Rights (ECHR). More specifically, the purpose of the thesis is to ex- amine if Sweden must regulate surrogacy to sufficiently protect individuals’ right to private and family life, enshrined in Article 8 ECHR. Furthermore, if such an obligation exists, is Sweden then also obliged to prohibit and crimi- nalize the practice? To answer these two questions, a traditional legal method will be used. The point of view of this thesis is to examine how these ques- tions would hypothetically be assessed by the European Court of Human Rights (ECtHR). Therefore, case law from the ECtHR is the main source em- ployed for this analysis. As the Court interprets the ECHR in light of other human rights instruments, other international conventions are also relevant to the discussion. The thesis identifies several risks of violations to rights protected by Article 8 that can be linked to surrogacy. Due to the limits of jurisdiction, Sweden can generally only be responsible to protect individuals within their territory from such risks. This means that the risk of exploitation of surrogates located abroad cannot trigger an obligation for Sweden to legislate. However, the ab- sence of a legal framework can create risks to other actors involved in the process that are under Swedish jurisdiction, namely children and commis- sioning parents. In the analysis of the thesis, it is concluded that these risks are of such nature that they trigger Sweden’s positive obligation to provide a sufficient legal framework. In the last part of the analysis, a discussion is had on what such a framework should look like. Here, it is found that there is no obligation to prohibit and criminalize surrogacy and such a framework could even itself constitute a violation of Article 8 ECHR. However, to secure pro- tection of the rights of the actors involved, a regulation that includes human rights standards can be introduced.
Keywords: public international law; surrogacy; ECtHR; ECHR; positive obligations; human rights